Economic Feasibility Analysis of Local Road Maintenance in West Bandung Regency: A Case Study of Cangkorah Street STA 0+000 – 1+300 - Juarti, Ery Radya; Sihombing, Atmy Verani Rouly; Pratiwi, Yola Widi; Fadillah, Sekar (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2023)
This study aims to determine the economic feasibility of local road maintenance scenario in West Bandung Regency with case study of the Cangkorah Street. After knowing the International Roughness Index (IRI) value based on the IKP value from the results of a direct survey using IKP guidelines, the economic feasibility analysis is carried out based on a road maintenance scenario, while the maintenance scenario being tested is a do-something scenario, by doing road maintenance in the form of overlay once every 5 years in 10 year time compared by a do-nothing scenario that is not doing any maintenance for the next 10 years. The research instruments used were prediction of the performance of the Cangkorah Street Pavement for the next 10 years, determine road maintenance scenarios, maintenance budget plans, calculate Vehicle Operational Costs (VOC) for each scenario, and time value. The results of this study are: (1) The budget plan for the maintenance of the Cangkorah Street in the do-something scenario with overlays 3 times in 10 years is Rp. 4,168,019,982, (2) The actual VOC for the do-nothing scenario was Rp. 57,345,718,978 and the actual VOC for the do-something scenario was Rp. 3,132,189,189 with VOC savings was Rp. 54,213,529,789, (3) The time value of the scenario for the next 10 years obtained savings of Rp. 399,241,414, (4) The feasibility of do-something scenario from an economic point of view shows that the scenario is feasible with a NPV of Rp. 36,674,480,627>0 and a BCR of 11,39 >1.